On-Surface Strain-Driven Synthesis of Nonalternant Non-Benzenoid Aromatic Compounds Containing Four- to Eight-Membered Rings - Mallada, Benjamin; de la Torre, Bruno; Mendieta-Moreno, Jesús I; Nachtigallová, Dana; Matěj, Adam; Matoušek, Mikulas; Mutombo, Pingo; Brabec, Jiri; Veis, Libor; Cadart, Timothée; Kotora, Martin; Jelínek, Pavel (Journal of the American Chemical Society, 2021)
The synthesis of polycyclic aromatic hydrocarbons containing various non-benzenoid rings remains a big challenge facing contemporary organic chemistry despite a considerable effort made over the last decades. Herein, we present a novel route, employing on-surface chemistry, to synthesize nonalternant polycyclic aromatic hydrocarbons containing up to four distinct kinds of non-benzenoid rings. We show that the surface-induced mechanical constraints imposed on strained helical reactants play a decisive role leading to the formation of products, energetically unfavorable in solution, with a peculiar ring current stabilizing the aromatic character of the π-conjugated system. Determination of the chemical and electronic structures of the most frequent product reveals its closed-shell character and low band gap. The present study renders a new route for the synthesis of novel nonalternant polycyclic aromatic hydrocarbons or other hydrocarbons driven by internal stress imposed by the surface not available by traditional approaches of organic chemistry in solution.